The Role of French Artisan Bakery Techniques in Shaping Culinary Tourism Experiences in India - Vanire , Shilpa; Srivastava , Adityaa; Deshmukh , Sajis; Shimpi , Ashish; Singh , Ajay; Soans , Oliver; Maira , Vandana (Journal of Neonatal Surgery, 2025)
The culinary tourism has gained significant niche in the world tourism categories because of the increasing curiosity of consumers in pure, culturally and experience food niche. The methods of French artisan bakery known to be accurate and of high quality and also a heritage have become a common aspect of the Indian life thus beginning to leave an impact on the food lives of India. The research problem that has been discussed in this study is how the techniques used by the French artisan bakery affect the culinary tourism experience of some of the metropolitan and heritage Indian cities. Data collection was done using mixed-methods, comprising of combination of structured questionnaires of tourists, in-depth interviews with bakery owners, on-the-job observations in the field in French-style bakeries and food festivals. The paper focuses on how these strategies impact authenticity in tourists, gastro satisfactions, and overall culinary experience. These findings indicate that the habits of French artisans in making bread, pastry, and ingredients and presentation concerns can significantly enhance the cooking experience of tourists as it is among the key branding points in the segmentation of the Indian cuisine. Through this paper, the researcher aims to bring out the importance of maintaining skills, cultural adjusting and experience storytelling as a marketing tool in culinary tourism. It disseminates data to restaurateurs, tourism policy makers, and culinary instructors who desire to integrate both international fine culinary abilities, and local culinary culture in an attempt to increase culinary tourism in India.